2010
DOI: 10.1021/ja1027524
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Nanoporous Silica with Periodic 30−60 nm Pores as an Effective Support for Gold Nanoparticle Catalysts with Enhanced Lifetime

Abstract: We demonstrate that supermolecular templating allows tuning the pore size of ordered mesoporous materials in the once elusive range from 30 nm to more than 60 nm through simple control of synthetic variables (salt/supermolecule concentration and hydrothermal temperature). Gold nanoparticles (AuNPs) within the extra-large pores exhibit dramatically increased lifetime compared to those located within relatively small mesopores due to the enhanced mass diffusion that suppresses coke deposition on AuNPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
102
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(107 citation statements)
references
References 14 publications
5
102
0
Order By: Relevance
“…AuNPs with a uniform size of 3.3 ± 0.5 nm were prepared according to our previous method ( Figure S1 in the Supporting Information). 20 They were readily adsorbed onto various supports by colloid deposition, followed by high-temperature thermal treatment. In a typical synthesis of AuCN materials, the supported AuNPs were transferred into a MeCN solution containing a certain amount of benzaldehyde for UV-light irradiation (λ > 300 nm) at room temperature (298 K).…”
Section: Resultsmentioning
confidence: 99%
“…AuNPs with a uniform size of 3.3 ± 0.5 nm were prepared according to our previous method ( Figure S1 in the Supporting Information). 20 They were readily adsorbed onto various supports by colloid deposition, followed by high-temperature thermal treatment. In a typical synthesis of AuCN materials, the supported AuNPs were transferred into a MeCN solution containing a certain amount of benzaldehyde for UV-light irradiation (λ > 300 nm) at room temperature (298 K).…”
Section: Resultsmentioning
confidence: 99%
“…Ma et al [159] recently reported the synthesis of gold catalysts supported on extra-large mesoporous silica material (EP-FDU-12), which were active and highly selective in the gas-phase oxidation of benzyl alcohol to benzaldehyde. The EP-FDU-12 support was prepared using Pluronic F127 as template agent and TEOS as silica precursor, in the presence of 1,3,5-trimethylbenzene and KCl.…”
Section: Synthesis By Dispersion Of Gold Colloids or Presynthesized Amentioning
confidence: 99%
“…22 For ordered mesoporous materials synthesized at high hydrothermal treatment temperature, it is frequently observed that the pore size determined by nitrogen adsorption is surprisingly larger than the cell parameter, and this phenomenon occurs in not only hexagonal mesostructures 23-25 but also OCMSMs. 7 In the case of hexagonal mesostructures, this observation was explained by the coalescence of adjacent mesopores 26 as confirmed by electron tomography (ET) technique. 25 However, for OCMSMs, this abnormal phenomenon is not well explained, further showing the limitation of nitrogen adsorption analysis in the determination of pore size.…”
mentioning
confidence: 94%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Introduction Ordered mesoporous materials (pore size in the range of 2-50 nm according to IUPAC classification) have received great scientific and industrial interest due to their large surface area, tunable pore structure as well as potential applications including separation, adsorption, filtration, and catalysis. [1][2][3][4][5][6][7][8][9][10][11] In particular, more attention has been paid to ordered cage-type mesoporous silica materials (OCMSMs) with controlled cages and entrance dimensions, such as SBA-16, FDU-1, KIT-5 and FDU-12, 1,3,8,11 due to their fascinating interconnected threedimensional structures. 2,10 During the last ten years, the synthesis of ordered cage-type mesoporous materials with tailored unit cell sizes, pore sizes and pore connectivity has been well reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation